Desisting from crime: continuity and change in long-term crime patterns of serious chronic offenders - Ezell, Michael E. (Clarendon studies in criminology, 2005)
This study examines patterns of offending among persistent juvenile offenders. Employing advanced quantitative techniques to offenders with very high rates of recidivism, Ezell and Cohen demonstrate that many of these apparently hardened criminals will 'grow out' of crime by the time they reach their 20s.